2011
DOI: 10.1002/smi.1418
|View full text |Cite
|
Sign up to set email alerts
|

Job Stress and Coping: Self‐Employed versus Organizationally Employed Professionals

Abstract: In order to examine job stress and coping among self-employed and organizationally employed professionals, job-related stressors and coping strategies were assessed among self-employed (n = 149) and organizationally employed (n = 159) professionals working as accountants, lawyers, pharmacists and psychologists. Results indicate that although self-employed workers complained about lack of security and organizationally employed workers complained about lack of autonomy, no differences were found in overall stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 34 publications
3
24
0
1
Order By: Relevance
“…Studies have found that self-employed workers are more prone to physical ailments and have more work-family conflicts than employees (Oren 2011), which may concur with the present finding that "own event" is a stressful event linked to depressive symptoms. In highly discretionary work, this may be similar to mental and physical health problems in self-employed work, which is a similar work style.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Studies have found that self-employed workers are more prone to physical ailments and have more work-family conflicts than employees (Oren 2011), which may concur with the present finding that "own event" is a stressful event linked to depressive symptoms. In highly discretionary work, this may be similar to mental and physical health problems in self-employed work, which is a similar work style.…”
Section: Discussionsupporting
confidence: 91%
“…Discretionary workers, who were the subjects of this study, are employed workers who are eligible for social insurance, but who also perform highly discretionary work, similar to self-employed workers. Previous studies indicated that lack of security is a stress factor for self-employed workers (Oren 2011). While discretionary workers do have security, household income may be more difficult to manage for them than for non-discretionary workers.…”
Section: Discussionmentioning
confidence: 99%
“…To be more precise, while active coping seeks to change the stressful situation, evasive coping is effective when it is difficult to change the situation or the stressors. For example, Oren (2012) notes that active coping is useful for employees with high levels of autonomy and control, but for those with limited capacity of control, active coping may be counterproductive for health due to the extra effort involved.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies such as Boyd and Gumpert (1983), Buttner (1992), Cardon and Patel (2015), Jamal (1997), and Andersson (2008) show that the owner faces higher stress levels than the employed. Mixed and nuanced results are shown in Algava et al (2012), Prottas and Thompson (2006), and Oren (2012), while Rahim (1996) and Baron et al (2016) identify owners with a lower stress level. Moreover, the discrimination between hindrance stressors (role conflict, role ambiguity, lack of resources, daily hassles, etc.)…”
Section: The Negative Consequences Of Small Business Ownership For Hementioning
confidence: 99%